Development of Three-Dimensional Space E-Module with Traditional Javanese Sundanese Culinary Ethnomathematics to Facilitate Students’ Mathematical Spatial Ability - Afiyanti, Yunita; Maryati, Tita Khalis; Hafiz, M. (International Journal of Geometry Research and Inventions in Education, 2025)
Mathematical spatial Ability is the ability of a person to imagine and represent a space. The lack of students' spatial mathematical abilities and the lack of variability of existing teaching materials to support mathematical learning became the background of this study. This study aims to produce e-modules using traditional Javanese Sundanese culinary ethnomathematics to facilitate students' valid, practical, and effective spatial mathematical abilities. The Research and Development method is used with the ADDIE development model (analyze, design, develop, implement, evaluate). The research was conducted on a limited basis by involving XII class students at one of the high schools in the Tajurhalang, Cibinong areas. The research instruments include expert validation sheets, student response metrics, and mathematical spatial ability tests. The results of this study show that the developed e-modules obtained very valid criteria based on expert validator assessments, were very practical based on student responses, and the results were valid. It is effective because students' spatial mathematical ability test results are higher than the school-designated Minimum Completeness Criteria (KKM), so e-modules are suitable for use in mathematical learning to facilitate students' spatial mathematical ability.